Journalistic Discours of A.G. Matoš – from Style to Political Imagery - Beck, Boris (Poznańskie Studia Slawistyczne, 2014)
In the newspaper articles and feuilltons, Antun Gustav Matoš uses a variety of procedures analogous to his artistic creation and develops a rich figuration and characteristic irony. The journalistic discourse constructed in that way consistently creates political and social imaginary which confirms oppositions: nationally/internationally, individual/collective, tradition/modernity and Croat/Serb, where the author clearly states his preference. Although Matoš consistently promote Starčevićʼs heritage, liberalism and individualism, he does not simply convey a political message, but adds meaning to agitation, which boosts its suggestivness, but also causes that it becomes relative.